Pengaruh PSAK 72: Pendapatan dari Kontrak dengan Pelanggan terhadap Shareholder Value - Sila Ninin Wisnantiasri (WIDYAKALA: JOURNAL OF PEMBANGUNAN JAYA UNIVERSITY, 2018)
This study aims to examine the impact of the Pernyataan Standar Akuntansi Keuangan (PSAK) 72 from shareholder’s perspective, published by Dewan Standar Akuntansi Keuangan Ikatan Akuntan Indonesia (DSAK IAI). Evaluation of stock market reaction applied to the industry sector more firms affected by the changed standars issuance, property, real estate and building contruction industry sector, because it replaces two standard at the same time used by this industry, that is PSAK 34 and PSAK 44. Measurement of stock market reaction based on shareholder value before and after the promulgation of the standard with event study approach. The result of this study provide empirical evidence that the promulgation of PSAK 72 increase shareholder value.They expect to reduce estimation risk by better information quality provided from financial statement because the accounting standard change.